2013
DOI: 10.1038/ejhg.2013.229
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in SH3PXD2B cause Borrone dermato-cardio-skeletal syndrome

Abstract: Borrone Dermato-Cardio-Skeletal (BDCS) syndrome is a severe progressive autosomal recessive disorder characterized by coarse facies, thick skin, acne conglobata, dysmorphic facies, vertebral abnormalities and mitral valve prolapse. We identified a consanguineous kindred with a child clinically diagnosed with BDCS. Linkage analysis of this family (BDCS1) identified five regions homozygous by descent with a maximum LOD score of 1.75. Linkage analysis of the family that originally defined BDCS (BDCS3) identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 23 publications
0
37
0
1
Order By: Relevance
“…However, we did not identify deleterious changes of SH3PXD2B or its homolog SH3PXD2A . Rather, we found a novel homozygous missense MMP14 mutation in these patients (Wilson et al, ). We recently reported that it mostly likely represents a hypomorphic allele (De Vos et al, ).…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…However, we did not identify deleterious changes of SH3PXD2B or its homolog SH3PXD2A . Rather, we found a novel homozygous missense MMP14 mutation in these patients (Wilson et al, ). We recently reported that it mostly likely represents a hypomorphic allele (De Vos et al, ).…”
Section: Introductionmentioning
confidence: 53%
“…Borrone, Di Rocco, Crovato, Camera, & Gambini () described two brothers with similar features. In these two patients, as well as in individuals previously diagnosed with FTHS, we identified homozygous mutations in SH3PXD2B (MIM #613293; Wilson et al, ).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Adult patients with this syndrome have been characterized as having acne conglobata with hypertrophic scarring and thickened skin . FTHS is inherited as an autosomal recessive trait and is caused by loss鈥恛f鈥恌unction mutations and deletions in SH3PXD2B on chromosome 5q35路1 . SH3PXD2B codes for TKS4, a tyrosine kinase substrate adaptor protein required for podosome maturation.…”
Section: Human Monogenic Disorders That Cause Acnementioning
confidence: 99%
“…68 FTHS is inherited as an autosomal recessive trait and is caused by loss-of-function mutations and deletions in SH3PXD2B on chromosome 5q35脕1. [69][70][71][72] SH3PXD2B codes for TKS4, a tyrosine kinase substrate adaptor protein required for podosome maturation.…”
Section: Frank-ter Haar Syndrome (Mim 249420)mentioning
confidence: 99%